The Relationship Between In-Service Teachers’ Mindset Types and Their Instructional Strategies - Yılmaz, Aslıhan (İstanbul Sabahattin Zaim Üniversitesi, 2020)
Mindset is the belief of whether people's abilities can be improved or not. It has been an essential phenomenon in education, and the value of this concept cannot be ignored in teachers' educational career. Teachers' mindset plays a pivotal role in learner achievement and building up self-esteem. On the other hand, there has not been much research done to examine teachers' mindset and teacher efficacy in instructional strategies. Thus, this study aims to investigate the relationship between in-service teachers' mindset types and their efficacy in instructional strategies. 130 EFL instructors who are teaching at the English Preparatory Program from state and foundation universities, which are located in Turkey, participated in this research. Teachers' Self-Efficacy Scale (TSES) and Teachers' Mindset Instrument (TMI) were used as data collection tools. TSES and TMS were found the most trustable and valid tools to measure the teachers' instructional strategies and their mindset. The reliability of the Teacher Mindset Instrument was measured as (a = 0.79). The reliability of Teachers' Self-Efficacy Scale was measured as (a= 0.86) for efficacy in instructional strategies. Pearson Correlation Analysis and Regression Analysis was conducted to reveal the relationship between teachers' mindset and teacher efficacy in instructional strategies. The results of the study indicate that there is a significant difference between teachers who have a growth mindset and a fixed mindset in terms of using instructional strategies. The teacher efficacy in the instructional strategies is more powerful when the teachers adopt growth mindsets. Researching these two concepts might contribute to teachers’ success in the future. Also, this study can shed light on the teacher development programs that universities will offer to their teachers.
İZÜ Sosyal Bilimler Lisansüstü Öğrenci Kongresi, 6-7 Haziran 2020 (ONLINE)
Keywords: Mindset; Self-efficacy Beliefs; English Language Teaching